Developments in handwriting and signature identification in the digital age - Harralson, Heidi H. (Forensic studies for criminal justice., 2013)
The examination of handwriting and signatures has a long and established history as a forensic discipline. With the advancement of technology in the use of digital tablets for signature capture, changes in handwriting examination are necessary. Other changes in handwriting, such as in increase in printed writing styles and the decrease in handwriting training in schools necessitates a re-examination of forensic handwriting identification problems. This text takes a fresh and modern look at handwriting examination as it pertains to forensic, legal, and criminal justice applications. About the Forensic Studies for Criminal Justice Series: The Forensic Studies for Criminal Justice series consists of short-format content on new developments, unique perspectives, or how-to information on areas in forensic science-all specifically designed to meet the needs of the criminal justice community. Instructors wishing to provide their students with more in-depth coverage on certain forensic areas can add these digestible, inexpensive works to their syllabi without having to completely redesign their course, introduce overly complex material, or financially overburden their students. Law enforcement and other criminal justice professionals will find a wealth of valuable information to improve training sessions. Written by experts in the disciplines they are covering and edited by a senior scholar in criminal justice, Forensic Studies for Criminal Justice opens up the world of forensic science to the criminal justice community. Part of a new Anderson series presenting brief works on forensic science, written especially for students and law enforcement. Delves into the latest research on the impact of computer use on handwriting. Focuses on fraud cases and related elder abuse.